Diversity, chorology and conservation of the grasses (Poaceae) in Serra do Ouro Branco, State of Minas Gerais, Brazil - Longhi-Wagner, Hilda Maria; Welker, Cassiano Aimberê Dorneles (Phytotaxa, 2012)
A survey of the Poaceae species that occur in Serra do Ouro Branco based on fieldwork and herbaria collections as well as bibliographical data is presented. Eighty-four species were found and are presented in a checklist. Five of these species were introduced to the area from Africa. Isachne (Micrairoideae) is a new record in the Espinhaço Range and Dichanthelium stipiflorum is a new record in the State of Minas Gerais. An analysis of the geographic distribution patterns of native species is presented together with a comparison with the Poaceae diversity on other mountains of the Espinhaço Range.